Dynamic changes in thalamic microstructure of migraine without aura patients: a diffusion tensor magnetic resonance imaging study. (7th November 2013) - Coppola, G.; Tinelli, E.; Lepre, C.; Iacovelli, E.; Di Lorenzo, C.; Di Lorenzo, G.; Serrao, M.; Pauri, F.; Fiermonte, G.; Bianco, F.; Pierelli, F.
<x xml:space="preserve">Abstract</x> Background and purpose The thalamus seems to be profoundly involved in the cyclical recurrence of migraine clinical and neurophysiological features. Here possible structural changes in the thalamus of migraineurs were searched for by means of diffusion tensor (DT) magnetic resonance imaging (MRI). This MRI technique provides quantitative data on water molecule motion as a marker of tissue microstructure. Methods Twenty‐four untreated migraine without aura (MO) patients underwent DT‐MRI scans (3‐T Siemens Gyroscan) during (n = 10) and between attacks (n = 14) and were compared with a group of 15 healthy volunteers (HVs). Fractional anisotropy (FA) and mean diffusivity (MD) were examined. Results During the interictal phase MO patients had a significantly higher FA and slightly lower MD values in bilateral thalami compared with HVs. During attacks, all MRI quantitative measurements in migraineurs were similar to those found in HVs. Right thalamic FA was positively correlated with the number of days since the last migraine attack in pooled patient data (r = 0.626, P = 0.003). Conclusions These higher thalamic FA values noted during the interictal period which normalized during an attack are probably related to plastic peri‐ictal modifications in regional branching and crossing of fibres. Whether these changes could be considered as the anatomical counterpart of the cyclical functional fluctuations previously observed in the neurophysiology of migraine remains to be determined.